Private Finance and Public Policy - Schinasi, Garry (IMF Working Papers; Working Paper ;, 2004)
This paper articulates a logical foundation-drawn from disparate literatures-for understanding why safeguarding financial stability is an important economic policy objective. The paper also explains why private aspects of finance provide broader social economic benefits and have the characteristics of public goods. Unique aspects of finance are examined, as are the linkages between finance, money, and the real economy. Sources of market imperfections in finance are identified and their implications are analyzed. The arguments imply that reaping the full private and social economic benefits of finance requires both private-collective and public-policy involvement as well as a delicate balance between maximizing the benefits of positive externalities (and public goods) and minimizing the costs (including potential instabilities) of other sources of market imperfections in finance.